'Because we're worth it': Young banlieue writers in France striving for inclusion. (1st July 2020) - Linn, Stella
French banlieue literature written by immigrant and 'post-migration' writers often involves a paradoxical mix of both 'high' and 'low' language varieties ‐ use of slang alternating with poetic utterances ‐ as well as references to popular culture alternating with 'high culture', which may range from American movies to intertextual references to canonized authors. What is the extratextual message of this intriguing mix, what do the predominantly young writers aim at, and what audience do they address in this way? By distinguishing four different strategies, this article argues that this hybrid blend is intended to act as a signal to the French reader, and thus indirectly to publishers and critics, that the writers conform to national standards and values, show full integration into French society, and therefore are entitled to claim a legitimate place in the French literary field.